2011
DOI: 10.1007/s11664-011-1801-z
|View full text |Cite
|
Sign up to set email alerts
|

Thermoelectric Properties of Polycrystalline Thin Films Under an External Magnetic Field

Abstract: A theoretical model is proposed to predict the Seebeck coefficient and the electrical conductivity for a polycrystalline thermoelectric (TE) thin film under an external magnetic field. The model considers the distribution of electrons in the microstructure of TE thin-film materials, taking the scattering effect of electrons at the grain boundary as the boundary condition for electron transport in the grain. The transmission coefficient is introduced to describe the probability of electrons passing through the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…High-performance TE generators mainly rely on the availability of high-quality TE materials [13][14][15][16][17]. Up to now, the researches on the high-performance TE generator are still not sufficient.…”
Section: Introductionmentioning
confidence: 99%
“…High-performance TE generators mainly rely on the availability of high-quality TE materials [13][14][15][16][17]. Up to now, the researches on the high-performance TE generator are still not sufficient.…”
Section: Introductionmentioning
confidence: 99%
“…Besides these radially heterogeneous nanostructures, more classical heterogeneous structures like laminates can show unusual properties when the thickness of layers decreases to several nanometers, like giant dielectric constants [8] or improved mechanical and electrical properties [9][10][11][12][13][14][15][16][17]. For these materials it is strongly suggested that the unusual effects originate from the surface/interface.…”
Section: Introductionmentioning
confidence: 99%